Microfinance and Village Economic Development: An Empirical Review - I Nengah Suarmanayasa; Sutarjo; Monica Feronica Bormasa; Nurlaila Hanum; Yeny Rokhilawati (CV Putra Publisher, 2026)
This study undertakes a qualitative systematic review of empirical research examining the nexus between microfinance and village economic development. Guided by the PRISMA framework and employing thematic synthesis, a total of 42 peer-reviewed studies published between 2000 and 2025 were analyzed. The synthesis reveals four overarching themes: (1) microfinance enhances access to capital and stimulates livelihood diversification; (2) it fosters women’s empowerment and strengthens village social capital; (3) institutional sustainability and governance challenges significantly moderate its effectiveness; and (4) under enabling conditions, microfinance generates multiplier effects that can catalyze structural transformation of rural economies. The findings demonstrate that while microfinance consistently contributes to household income, asset accumulation, and microenterprise growth, its translation into village-wide economic development is neither automatic nor uniform. Positive transformation is contingent upon complementary interventions, including financial literacy training, market linkages, robust local governance, and synergy with village development programs. The review underscores that microfinance should be positioned as a catalyst within an integrated rural development framework rather than a standalone panacea. This evidence base offers actionable insights for policymakers and practitioners aiming to leverage inclusive finance for sustainable village development